Acute Kidney Injury in The Intensive Care Unit: A Case Study at RSUD Dr. Chasan Boesoirie Ternate - Albaar, Muhamad Taha; Masrika, Nur Upik En (Eduvest - Journal of Universal Studies, 2025)
This study aimed to analyze the factors influencing the incidence of Acute Kidney Injury (AKI) in the ICU of Dr. H. Chasan Boesoirie Hospital, Ternate, North Maluku. The research utilized a cross-sectional design involving 53 ICU patients diagnosed with AKI, examining the relationship between risk factors such as diabetes mellitus, hypertension, and the severity of AKI. Data was collected through medical record reviews. The results revealed that most AKI patients were over 60 years old, with a high mortality rate. Diabetes mellitus was found to be less common among AKI patients in this study, contrary to findings from other regions in Indonesia. This research emphasizes the importance of early detection and addressing comorbidities in preventing and managing AKI. The findings suggest a need for improved healthcare systems and early interventions, especially in underserved areas.